2020
DOI: 10.3389/fpsyg.2020.580730
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors Influencing Pro-environmental Behavior in Developing Countries: Evidence From Colombian and Nicaraguan Students

Abstract: Identifying the determinants of human behavior is useful to adjust interventions and lead the civil society toward a stronger commitment to climate change (CC) mitigation and adaptation objectives, achieving greater support for successfully implementing environmental policies. Existing research has largely focused on case studies of pro-environmental behaviors (PEBs) in developed economies but there is very little evidence for developing countries. This study provides estimations of the effect of internal fact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 98 publications
2
21
0
2
Order By: Relevance
“…Whereas another study determined the sense of pride as an essential factor behind pro-environmental behaviour no guilt feeling (Bissing-Olson et al, 2016). Similar findings derived from other studies where moral values, social norm, attitude and behavioural control examined to be important factors for initiating and continuing pro-environmental behaviour (Moser, 2015;Bamberg & Möser, 2007;Chen et al, 2018;Culiberg & Elgaaied-Gambier, 2016;Díaz et al, 2020;Esfandiar et al, 2020;Esfandiar et al, 2019). The affiliation between social and personal factors with pro-environmental behaviour was unearthed in many other studies as well (Gifford et al, 2014, Kollmuss & Agyeman, 2002, Kulin & Sevä, 2021, Wu, et al, 2021.…”
Section: Introductionsupporting
confidence: 67%
“…Whereas another study determined the sense of pride as an essential factor behind pro-environmental behaviour no guilt feeling (Bissing-Olson et al, 2016). Similar findings derived from other studies where moral values, social norm, attitude and behavioural control examined to be important factors for initiating and continuing pro-environmental behaviour (Moser, 2015;Bamberg & Möser, 2007;Chen et al, 2018;Culiberg & Elgaaied-Gambier, 2016;Díaz et al, 2020;Esfandiar et al, 2020;Esfandiar et al, 2019). The affiliation between social and personal factors with pro-environmental behaviour was unearthed in many other studies as well (Gifford et al, 2014, Kollmuss & Agyeman, 2002, Kulin & Sevä, 2021, Wu, et al, 2021.…”
Section: Introductionsupporting
confidence: 67%
“…Results also denote a greater sensitivity of college students to perform this type of behavior (Doherty & Clayton, 2011), which is relevant if we ponder that this population may play an important role in environmental decision-making in their professional and public life (Díaz, et al, 2020).…”
Section: Resultsmentioning
confidence: 83%
“…Lo encontrado denota también una mayor sensibilidad de los estudiantes universitarios para ejecutar este tipo de conductas (Doherty & Clayton, 2011), lo cual es relevante si se toma en cuenta que dicha población puede jugar un rol importante en la toma de decisiones ambientales dentro de su vida profesional y pública (Díaz, et al, 2020).…”
Section: Resultsunclassified
“…Besides that, [9] and [10] studied the green purchasing behaviors in Germany and Vietnam respectively. [11] did research on students' consumption intentions of genetically modified food at a university in China, and study from the Indonesia [12], and other developing countries such as Colombian and Nicaraguan [13] have also been found. Studies based on Malaysian recycling behaviors [14] have also been found.…”
Section: Introductionmentioning
confidence: 99%